Science and Football VIII The Proceedings of the Eighth World Congress on Science and Football (Taylor & Francis, 2017)
Science;Football;Congresses;Physiological;Soccer
English
Keywords: Science: general issues; Sport & the law; congresses; football; physiological; science; soccer